Sviluppo economico e divisione territoriale del lavoro: il caso FIAT - Michael Dunford; Lidia Greco (Quaderni di Sociologia, 2007)
This article considers economic development from a theoretical perspective that emphasises the role of the profit and upgrading strategies of capitalist enterprises and the evolution of the territorial division of labour. After an initial consideration of the existing literature on value chains, value chain upgrading and on the territorial division of labour, it is argued that the evolution of the territorial division of labour should be examined in the light of the strategies of profit-seeking firms and their economic performance. Enterprise strategies and performances, which are themselves influenced by the wider institutional environment, are seen as some of the most important drivers of in situ change in the profile of employment and income and also of the location of different but interdependent parts of value chains in different contexts with different costs, skills, supporting services and research infrastructures. In this perspective, cultural approaches to economic development should be seen as complementary and not as an alternative to more structuralist stances. From a methodological perspective, the article offers indicative interpretations of territorial development trends through an analysis of the sectoral profile of regional economies and the strategies of lead firms within some of those sectors. To illustrate this theoretical approach the article concludes with a case study of FIAT in Piemonte and Basilicata.